Government Intervention and Adverse Selection Costs in Foreign Exchange Markets - Naranjo, Andy; Nimalendran, M. (Review of Financial Studies, 2000)
An important group of traders in the foreign exchange market is governments who often adhere to a foreign exchange rate policy of occasional interventions with otherwise floating rates. In this article we provide a theoretical model and empirical evidence that government foreign exchange interventions create significant adverse selection problems for dealers. In particular, our model shows that the adverse selection component of the foreign exchange spread is positively related to the variance of unexpected intervention and that expected intervention has no impact on the spread. After controlling for inventory and order processing costs, we find that bid-ask spreads increase with U.S. dollar and German deutsche mark foreign exchange rate intervention during the period 1976–1994. Furthermore, when the intervention is decomposed into expected and unexpected components, we find a statistically and economically significant increase in spreads with the variance of unexpected intervention, while expected intervention has no significant impact on spreads.